Human Cu/Zn superoxide dismutase gene family: molecular structure and characterization of four Cu/Zn superoxide dismutase-related pseudogenes. - Danciger, E (1986)
Four distinct human Cu/Zn superoxide dismutase (SOD1; EC 1.15.1.1)-related sequences were isolated from genomic DNA libraries. Genomic blots, heteroduplex analyses, and DNA sequencing showed that they are processed pseudogenes not residing on chromosome 21. Three of them originated from the 0.7-kilobase SOD1 mRNA, while the fourth was derived from the 0.9-kilobase mRNA species. Comparison between the coding sequences of the functional gene and two of the processed genes suggested that they integrated into the genome about 25 million years ago.